The Information System for Improving the Effectiveness of ECE Services During the COVID-19 Pandemic - Subhan, Subhan (Al-Athfal: Jurnal Pendidikan Anak, 2022)
Purpose – The pandemic-era policy that requires schools to conduct face-to-face meetings is an issue that cannot be taken "lightly". The trend of face-to-face learning that has entrenched makes schools, including ECCE institutions, "profitable". There are not many alternatives that can be done, other than using online face to face applications that have been popular such as Whatsapp and other Messanger. However, the use of these applications cannot cover all Early Childhood Education (ECE) learning needs with their own characteristics that are generally different from learning at other levels of education. Therefore, a more suitable online learning system is needed such as through the Si-Pappa Information System/Application. Design/methods/approach – For this purpose, in this study, the PAR (Participation Action Research) Method was used with assisted objects, namely 10 ECE Institutions in Palopo City which have been partners of the Islamic Early Childhood Education IAIN Palopo Study Program. Data collection methods utilizing Performance Tests are reinforced by unstructured interviews and direct observation. Findings – The results of data analysis, the parameters of the results of the implementation of service were achieved, namely the average participant who was able to master the parameters of more than 83%. From this, it can be concluded that the Application of Information Systems (Si-Pappa) can improve the effectiveness of ECCE services during the pandemic in Palopo City. Research implications/limitations – This study related to the problems of learning effectiveness during the COVID-19 pandemic.  Practical implications – The use of the Si-Pappa application allows parents to conduct direct and measurable consultations from the existing menu, making teachers provide methodical assistance because the video calls made are directly integrated into each participant's account so that it can be directly reviewed or confirmed from other menus such as autentic assessment conditions that show photos of children, flow charts or worksheets of learning activities, anecdotal notes related to special or unique conditions of children, and various other comparative data that can be used in determining mood conditions, causes used in making decisions to follow up to determine a wiser and more comprehensive solution for children. Originality/value – The impact of teacher understanding of the concept of learning from home in the context of using applications is that teachers not only view learning applications such as Si-Pappa only as learning tools or media, but are able to appreciate the presence of applications as assistance partners that will make learning more effective. Paper type Research paper